P158 Performance of laser-derived imaging for assessing digital perfusion in clinical trials of systemic-related digital vasculopathy: a systematic literature review. (26th April 2021) - Hackett, Natalia; Guida, Andrea; Pauling, John D; Merkel, Peter A
Abstract: Background/Aims   Raynaud's phenomenon (RP) and digital ulcers (DU) are important features of digital vasculopathy in systemic sclerosis (SSc). Laser Doppler flowmetry (LDF), laser Doppler imaging (LDI) and laser speckle contrast imaging (LSCI) can non-invasively quantify digital perfusion and may be useful outcome measures for clinical trials in SSc-RP and/or SSc-DU. We undertook a systematic literature review to evaluate the performance of laser-derived imaging as outcome measures in clinical trials of SSc-related digital vasculopathy. Methods   Standardised searches (EMBASE and MEDLINE) identified trials that incorporated laser-derived imaging of digital vasculopathy in adult patients with SSc. Data were extracted by > 2 reviewers on study design, laser endpoints, and reported outcomes. Study quality was assessed using Cochrane risk of bias tools for randomized trials and the risk-of-bias assessment tool for non-randomized studies (RoBANS) (PROSPERO 2019:CRD42019142409). An additional search was undertaken following external peer review to examine the impact of extending the search terms. Results   Of 126 identified articles, full data extraction was undertaken from 29 studies. Fifteen randomized and fourteen non-randomized trials (total of 689 patients with SSc with mean 23.8/study) have evaluated a broad range of oral, intravenous and topical interventions for SSc-RP (n = 11), digital perfusion alone (n = 15) and SSc-DU (n = 3). The extended search identified an additional two manuscripts reporting the use of LDF to measure perfusion of a single digit in SSc. One was a randomised trial (of 25 patients) and the second an open label study (of 13 patients). These additions did not alter the principal findings of the main review. Combining the two searches, the 31 studies were published between 1987-2019 (17/31 since 2010) and incorporated LDF (13/31), LDI (15/31) and LSCI (4/31, including one with LDF); with LSCI and LDI more commonly incorporated in recent trials (13/18 since 2010). Most studies (17/31, 55%) reported improvement in digital perfusion following intervention, often concordant with patient- and clinician-derived outcomes. Study quality has improved over time, with 7/11 studies published between 2015-2019 having low risk of bias across all study quality domains. Conclusion   Establishing laser-derived methods as an objective, non-invasive assessment of SSc-related digital vasculopathy will greatly support drug development. Full-field perfusion of the digits (with/without provocation testing) is a promising clinical trial outcome measure for trials of SSc-related digital vasculopathy. Disclosure   N. Hackett: None. A. Guida: None. J.D. Pauling: Consultancies; Boehringher-Ingelheim, Sojournix Pharma and Actelion pharmaceuticals. Honoraria; Actelion pharmaceuticals. Grants/research support; Actelion pharmaceuticals. P.A. Merkel: Consultancies; AbbVie, AstraZeneca, Biogen, Boeringher-Ingelheim, Bristol-Myers Squibb, Celgene, ChemoCentryx, CSL Behring, Forbius, Genentech/Roche, Genzyme/Sanofi, GlaxoSmithKline, InflaRx, Insmed, Jannsen, Kiniksa, Pfizer, Sparrow, and Talaris. Grants/research support; AstraZeneca, Boeringher-Ingelheim, Bristol-Myers Squibb, Celgene, ChemoCentryx, Forbius, Genentech/Roche, Genzyme/Sanofi, GlaxoSmithKline, InflaRx, Kypha.